Dietary supplementation with Gracilaria gracilis by-products modulates the immune status and oxidative stress response of gilthead seabream (Sparus aurata) stimulated with Photobacterium damselae subsp. piscicida. Issue 126 (July 2022) - Silva-Brito, Francisca; Cardoso, Alexandra; Machado, Marina; Ramos-Pinto, Lourenço; Hinzmann, Mariana; Abreu, Helena; Costas, Benjamín; Magnoni, Leonardo
Abstract: This study evaluated the effects of agar waste (AW) dietary supplementation, obtained from the seaweed Gracilaria gracilis cultivated under two different spectral lights, neutral (NT) and blue (BL), on haematological parameters, inflammatory response, and antioxidant biomarkers of gilthead seabream ( Sparus aurata ). Three diets were prepared: i) a basal diet (CTR), ii) a diet supplemented with 2.5% NT, and iii) a diet supplemented with 2.5% BL. After 15 days of feeding, fish were injected with PBS (placebo) or inactivated Photobacterium damselae subsp. piscicida (stimulated) and sampled at 4 h and 24 h post-stimulus. Results indicated that fish fed NT and BL supplemented diets had lower Ht value and mean corpuscular volume (MCV) than fish fed the CTR diet, regardless of the stimulus and the sampling time. No differences in mean corpuscular haemoglobin (MCH) were found between fish fed the different diets, while the mean corpuscular haemoglobin concentration (MCHC) increased in fish fed AW supplemented diets compared to fish fed the CTR diet, regardless of the stimulus and the sampling time. In response to inflammation, fish fed the NT diet displayed higher neutrophils count in blood when compared to the CTR group, regardless of the stimulus and sampling time. Thrombocyte count was higher in fish fed NT and BL diets than in the CTR group, especially in the stimulated fish (Diet*injection (D*I), P = 0.004). An increase in plasma protease activity was detected in fish fed NT or BL diets in both placebo and stimulated fish regardless of the sampling time. Hepatic catalase activity was higher in fish fed the NT and BL than in the CTR group, particularly in the stimulated fish (D*I, P < 0.001). In addition, both stimulated and placebo fish that received the BL diet showed an increase in hepatic GR activity compared to the CTR group, regardless of the sampling time. Dietary supplementation with AW by-products obtained from G. gracilis cultured under NT and BL conditions showed to improve the inflammatory and antioxidant mechanisms in gilthead seabream in response to a UV-killed bacterial stimulus, having valuable applications for the sustainable use of seaweed toward improving the health and welfare of cultured fish. Highlights: ·Dietary supplementation with 2.5% AW (BL and NT) improved the haematological parameters of gilthead seabream. NT enhanced the inflammatory response by increasing the peripheral neutrophil count. AW improved the humoral response by increasing the plasma protease activity. AW differently modulated the antioxidant system response in the liver and the intestine of fish.